Normative Gaps and Reconstruction of Legal Accountability Diagnostic AI in Indonesia's Healthcare Sector - Pretty Kristianti Dewi; Eva Christine; Oktavia Hutapea; Mira Puspitasari; Irman Putra; Chandra Matdung Wira Pramukanta (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
The use of artificial intelligence (Artificial Intelligence/AI) in the healthcare sector has developed very rapidly and is increasingly being applied in various medical services. This condition poses new challenges for the legal system, since the existing legal framework was basically designed to regulate human actions and responsibilities. As AI increasingly assists and even replaces some functions of medical personnel, legal regulation is required to adapt to these changes. Clarity regarding the legal status of AI in healthcare is crucial for determining which party must be responsible when losses arise from the use of this technology. Advances in AI technology have produced various algorithm-based diagnostic systems capable of improving the speed, efficiency, and accuracy of healthcare services. However, these technological developments have not been matched by adequate legal arrangements, particularly with regard to liability for diagnostic errors generated by AI systems. This research aims to examine normative gaps in Indonesian health law concerning the use of AI and to formulate a concept of digital accountability regulation that is more responsive to technological development. The method used is normative juridical research using statutory, conceptual, and comparative approaches. The findings show that regulatory deficiencies remain in determining responsible parties, accountability standards, and oversight mechanisms for the implementation of AI in the medical field. Therefore, legal reform is required through the development of a layered liability model and risk-based regulation grounded in the principles of transparency, auditability, and the protection of patient rights and safety.